Integrated Marketing Communication in Project Activities - Lacković, Krešimir (Array, 2021)
The paper deals with integrated marketing applied in project activities. The reason for this is the fact that such activities should refine their offer with a supplement in the project documentation but in the means of a different approach to the market. The amendment addresses recommendations to investors for the future construction and maintenance of facilities, and Lean and BIM in the design, construction and maintenance of facilities. That is why, during market processing, investors are offered an offer that solves the project task, includes design with visualization, and construction supervision, but already at this stage also includes certain maintenance solutions. This is only possible if the customers are approached comprehensively. For this there is an integrated marketing activity or process, where already in the market research, customers are informed about a kit containing everything from design, through construction to maintenance of the facility. Successful application of this process requires appropriate hardware and software support, as well as trained personnel for marketing. In scientific terms, a new method of integrating marketing activities in the business process of project activities is proposed. In application terms, a business process organization model integrated with marketing is presented, which enables the project company to connect with the market more dynamically and efficiently.